High resolution electronic spectroscopy of small molecules - Duxbury, Geoffrey
"Electronic spectroscopy has developed significantly, with key uses in atmospheric chemistry, astrophysics, and astrochemistry. This book is the first to cover both theoretical and experimental spectroscopy of small molecules. It examines the links between spectroscopy and photochemistry, discusses theoretical treatments of the interaction between different electronic states, and discusses experimental techniques at length. Practical applications covered include exhaust gas measurements in aircraft turbines, pollution, free radicals, global warming, low temperature plasmas, and ionization effects in giant gas planets"--